What Kinds of Departments Promote Undergraduate Research in Political Science?. Issue 3 (3rd July 2021) - Ishiyama, John
Abstract: In this paper, I examine the factors that are associated with the adoption of a formalized undergraduate research program in political science. What kinds of institutions and departments are more or less likely to adopt a formalized undergraduate research program? One the one hand, one might assume that such a program appears in departments that are well endowed with research resources, i.e. Ph.D. granting departments. On the other hand, the personal interaction between faculty members and undergraduate students required of mentored undergraduate research might suggest such programs are more likely to exist at primarily undergraduate degree-granting programs. Using data from the 2017 to 18 American Political Science Departmental Survey of 383 political science departments, I find that contrary to expectations, institutional characteristics are unrelated to the likelihood of offering an undergraduate research program. Rather the one factor that is significantly related to whether a department offers an undergraduate research program is whether the department also offers a capstone course as an indicator of a structured curriculum. This suggests a commitment to curricular structure is most associated with the promotion of undergraduate research, independent of institutional characteristics.